Rhodium-catalyzed ortho-heteroarylation of phenols: directing group-enabled switching of the electronic bias for heteroaromatic coupling partner. Issue 33 (25th July 2018) - Wu, Yimin; Li, Wei; Jiang, Linfeng; Zhang, Luoqiang; Lan, Jingbo; You, Jingsong
Abstract : A highly efficient ortho -heteroarylation of phenols with diverse electron-rich heteroarenes has been developed to forge heteroaryl-2-hydroxyphenyl structural motifs. The removal of the directing group and subsequent intramolecular cyclization make this protocol applicable in the rapid construction of π-conjugated heteroacenes. Abstract : The directed oxidative C–H/C–H cross-coupling reactions between a functionalized arene and a heteroarene typically exhibit an electronic bias for the heteroaromatic coupling partner. Disclosed herein is a conception of directing group enabled-switching of the electronic bias for coupling partner from the electron-deficient to electron-rich heteroarene, demonstrating that the modification of the directing group may match the latent reactivity of heteroarene substrates caused by the distinctly different electronic nature. In this work, we develop a Rh(iii )-catalyzed ortho -heteroarylation of phenols with greatly important electron-rich heteroarenes such as benzothiophene, benzofuran, thiophene, furan and pyrrole via two-fold C–H activation, which presents broad substrate scopes of both phenols and electron-rich heteroarenes and shows the advantage of tolerance of reactive functional groups, especially halogen. This work also provides a new strategy for the construction of π-conjugated furan-fused heteroacenes prevalent in materials science in dramatically simplified procedures, which makes the protocol highly applicable.